Evaluation of structural and optical properties of graphene oxide-polyvinyl alcohol thin film and its potential for pesticide detection using an optical method - Muhamad Fauzi, Nurul Illya; Fen, Yap Wing; Abdullah, Jaafar; Ahmad Kamarudin, Mazliana; Sheh Omar, Nur Alia; Kamal Eddin, Faten Bashar; Md Ramdzan, Nur Syahira; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim (Multidisciplinary Digital Publishing Institute, 2022)
In the present work, graphene oxide (GO)–polyvinyl alcohol (PVA) composites thin film has been successfully synthesized and prepared by spin coating techniques. Then, the properties and morphology of the samples were characterized using Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis), and atomic force microscopy (AFM). Experimental FTIR results for GO–PVA thin film demonstrated the existence of important functional groups such as -CH2 stretching, C=O stretching, and O–H stretching. Furthermore, UV-Vis analysis indicated that the GO–PVA thin film had the highest absorbance that can be observed at wavelengths ranging from 200 to 500 nm with a band gap of 4.082 eV. The surface morphology of the GO–PVA thin film indicated the thickness increased when in contact with carbaryl. The incorporation of the GO–PVA thin film with an optical method based on the surface plasmon resonance (SPR) phenomenon demonstrated a positive response for the detection of carbaryl pesticide as low as 0.02 ppb. This study has successfully proposed that the GO–PVA thin film has high potential as a polymer nanomaterial-based SPR sensor for pesticide detection.